Revisit Study of Freshwater Sponges Eunapius carteri (Bowerbank, 1863) and a New Record of Oncosclera asiatica Manconi and Ruengsawang, 2012 (Porifera: Spongillida) in Porong River, East Java, Indonesia - Setiawan Edwin; Yanuar Ahmad; Michael Einstein Hermanto; Riani Catur; Prayogo Fitra Adi; Budiharjo Anto (HAYATI Journal of Biosciences, 2023)
Distribution of freshwater sponges (Porifera: Spongillida) in Indonesia is currently insufficiently reported and underestimated compared to marine sponges. An inventory study on freshwater sponges in East Java after Indonesian independence in 1945 is yet to be carried out. For this reason, we reported new records of two freshwater species, Eunapius carteri (Bowerbank, 1863) and Oncosclera asiatica (Manconi and Ruengsawang, 2012) in Porong river, East Java, Indonesia. E. carteri species was originally described in Mumbai, India and its presence in Java was reported in 1927, 1928, and 1930. DNA barcoding and molecular phylogenetic analysis using mitochondrial COI was able to successfully identify our specimens as E. carteri, while analysis using the nuclear ITS markers placed our samples with other Eunapius species. Furthermore, in this study we report for the first time in East Java, Indonesia, the presence of O. asiatica. The O. asiatica species was originally described from Pong River located in Lower Mekong, Thailand. We concluded our specimens to be O. asiatica based on the morphology, skeleton, and spicule composition of the specimens that were similar to the samples recorded in Thailand. We were only successful in obtaining the COI sequence of O. asiatica. Furthermore, our samples did not group to the publicly available sequence of its congener, namely Oncosclera sp. Therefore, further molecular taxonomy and morphological analysis is needed to explore the diversity of freshwater sponges in general and to conduct species delimitation of E. carteri and O. asiatica in Java, Indonesia, and Asia